French espionage and counter-espionage during the Algerian War of Independence through Operation Blue Bird (1955-1956) - kasri, mohamed said (The Algerian Historical Journal, 2026)
The Algerian revolution witnessed several intelligence operations carried out by the French colonial intelligence; within the framework of what was known as French espionage, which was given several names: the important case, Force K, the conspiracy, Commando K...etc. The Algerian revolution countered this with a counter-espionage operation called "Blue Bird." This operation took place in the historical Third Province, specifically in the Kabylie region. The goal was to undermine the revolution from within, having failed to crush it militarily. What were the events and facts of this intelligence operation, and to what extent did the Algerian revolution succeed in countering it?